Women Scientists as Decor: The Image of Scientists in Spanish Press Pictures. (August 2017) - González, David; Mateu, Anna; Pons, Empar; Domínguez, Martí
Women are still less present in scientific areas than men. This study analyzes the visual representation of women scientists in Spanish press and concludes that they are also underrepresented in newspapers. We analyze 1, 134 photographs published in 2014 and 2015 in the science news sections of the four largest distribution Spanish newspapers. A tendency to present men more often as the protagonists of the information and women as a visual resource is also observed. This text proposes the need for the media to be aware of such underrepresentation and to match the number of men and women in graphic materials.